NNLO PDFs driven by top-quark data - S. Alekhin; M. V. Garzelli; S.-O. Moch; O. Zenaiev (European Physical Journal C: Particles and Fields)
Abstract We study the impact of state-of-the-art top-quark data collected at the large hadron collider on parton distribution functions (PDFs). Following the ABMP methodology, the fit extracts simultaneously proton PDFs, the strong coupling $$α _s(M_Z)$$ α s ( M Z ) and heavy-quark masses at next-to-next-to-leading order (NNLO) accuracy in QCD. It includes recent high-statistics data on absolute total inclusive cross sections for $$t\bar{t}+X$$ t t ¯ + X , the sum of $$(t + X)$$ ( t + X ) and $$(\bar{t} + X)$$ ( t ¯ + X ) hadroproduction, and normalized inclusive data double-differential in the invariant mass and rapidity of the $$t\bar{t}$$ t t ¯ pair at $$\sqrt{S}=13$$ S = 13 TeV. The gluon PDF at large x and the top-quark mass value derived from these data are well compatible with the previous ABMP16 results, but with significantly smaller uncertainties, reduced by up to a factor of two. At NNLO in QCD we obtain for the strong coupling the value $$α _s^{(n_f=5)}(M_Z)= 0.1150 ± 0.0009$$ α s ( n f = 5 ) ( M Z ) = 0.1150 ± 0.0009 and for the top-quark mass in the $${\overline{\text{ MS }}}$$ MS ¯ -scheme $$m_t(m_t) = 160.6 ± 0.6$$ m t ( m t ) = 160.6 ± 0.6 GeV, corresponding to $$m_t^pole = 170.2 ± 0.7$$ m t pole = 170.2 ± 0.7 GeV in the on-shell scheme. The new fit, dubbed ABMPtt, is publicly released in grids in LHAPDF format.